ARDS with septic shock managed successfully using a multidisciplinary approach: A case report (Indian Journal of Case Reports, 2024)
Acute respiratory distress syndrome (ARDS) is an inflammatory process in the lungs that results in hypoxemia and decreased lung compliance. Invasive mechanical ventilation and prone positioning have proven benefits in the management of patients with severe ARDS. Post-extubation rehabilitation programs are equally important for the recovery of these patients. We are reporting the case of a 30-year-old male with severe ARDS where lung protective ventilation, timely intubation, early prone positioning, multidisciplinary communication, and post-discharge follow-up with teleconsultation were used under expert supervision in the successful management of the case.